Proceedings of the Royal Society of Medicine. - Royal Society of Medicine (Great Britain) (London, Royal Society of Medicine [etc.], 1907)
Comprises the proceedings of the various sections of the society, each with separate t.p. and pagination.
Chemical abstracts
Vols. 1-21 consist of 3 pts. each, v. 22- of 2 pts. each.
Mode of access: Internet.
UCLA Library - CDL shared resource.
Keywords: Royal Society of Medicine (Great Britain) -- Periodicals; Royal Society of Medicine (Great Britain) -- Periodicals; Medicine -- Congresses; Medicine -- Periodicals